DRAFT MODEL MONITORING AND COLLECTIONMINIMIZE EFFORTS IN POTENTIAL LOSS ACCEPTANCE OF DUTY ACQUISITION OF LANDAND BUILDING ( BPHTB ) AS A REGIONAL TAXDISTRICT KETAPANG ( AFTER LAW ENFORCEMENTNUMBER 28 OF 2009 ) - B61110054, IWAN KUSNADI (Jurnal Ekonomi Daerah (JEDA), 2015)
This study aims to determine the potential loss BPHTB, to know what efforts can be done by the district ketapan in optimizing BPHTB, as well as to determine the design of the monitoring and collection of models in an effort to minimize potential losses BPHTB. The method used in this research is "Descriptive Analysis" by using secondary data and primary data. The cause of potential losses revealed by observation acceptance. Strategies for optimizing BPHTB developed using SWOT analysis. The model that was designed in an effort to minimize the reception Loss Potential Acquisition Fee Land and Building (BPHTB) is by using a flowchart. The results showed that revenues in the six districts BPHTB ketapan district has happened potential loss of 50.06% in 2011 due to dishonesty taxpayer behavior, and also less involvement of the Notary / PPAT in assisting local governments to criminalize buying and selling among the community. The model that was designed in an effort to minimize potential losses BPHTB among others: (1) Formulate and establish local regulations on BPHTB, (2) Updating SVTO prices that are not in accordance with current conditions, (3) Publish and disseminate the regulations relating to the implementation of the collection BPHTB various media, (4) Simplify and streamline complex organizational structure so as to facilitate service and will be quick, (5) There is a high commitment and honest with each implementer, (6) The presence of qualified and motivated staff who high, (7) Sufficient financial resources and the physical facilities that computerized. With the fulfillment of the elements described above, will facilitate the achievement of the process in an effort to minimize potential losses BPHTB in Ketapang district. Keywords : Strategy, Potential Loss, Tax.